Perception of the Citizen Safety in inhabitants from Arequipa City District - Huamani Cahua, Julio Cesar (2019)
The study analyzes the perception of citizen security in 444 settlers from the district of Paucarpata of the City of Arequipa, chosen randomly. The average age of the participants (M = 28.6, SD = 13) years, of which 47.1% are male and 52.9% are female. The instrument used was the Citizen Security Questionnaire. The results indicate low perception of citizen security and its dimensions (Reliability, Empathy and Tangible Elements), and there are statistically significant differences in the response capacity between men (M = 15.7, DE = 4.2) and women (M = 16.9). ; DE = 4.2), these differences being small TE (d = 0.29). In addition, the participants who are single, students and with a higher education degree, have a better perception about the variable under study than the other groups of participants, however, these differences have TE small. Age correlates in an inverse and low way with the dimensions and variable studied, that is, younger participants have a better perception of citizen security, unlike older participants.